2006
DOI: 10.1021/jp0626824
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopy and ab Initio Studies of Lithium Bis(oxalato)borate (LiBOB) in Different Solvents

Abstract: The effect of lithium ion coordination with the bis(oxalato)borate (BOB -) [B(C 2 O 4 ) 2 ]anion in DMSO, PEG, PPG, and d-PPG has been studied in detail by IR and Raman spectroscopy. Ab initio calculations were performed to allow a consistent analysis of the experimental data. The main features observed in the IR and Raman spectra correspond to the presence of "free", un-coordinated, BOBanions. Only with use of d-PPG as solvent a small amount of Li + ‚‚‚BOBion pairs were detected. The Raman spectra and the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 46 publications
4
27
0
1
Order By: Relevance
“…It is also observed that the peak intensity gradually increased with the increase of LiDFOB salt in polymer-salt complex. The BOB¯anion also possessed these C═O bonds reported by Holomb et al [29]. The other peaks of pure LiDFOB salt (Fig.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 70%
“…It is also observed that the peak intensity gradually increased with the increase of LiDFOB salt in polymer-salt complex. The BOB¯anion also possessed these C═O bonds reported by Holomb et al [29]. The other peaks of pure LiDFOB salt (Fig.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 70%
“…The Fourier transform infrared (FTIR) (Fig. 1) spectrum confirms the fundamental vibrational modes of the LiBOB salt and its assignments are presented in Table 2; a similar type of report is given by Holomb et al [16].…”
Section: Synthesis Of Libobsupporting
confidence: 78%
“…Fonseca et al [8], for the first time, prepared the PCL:LiClO 4 -based polymer electrolyte for rechargeable batteries. Due to its low cost, low toxicity, stability, and ease of preparation, lithium bis(oxalato)borate (LiBOB) is currently being evaluated as a suitable salt for use in lithium ion battery technology [10]. Also compared with other Li salts, LiBOB salt has low lattice energy making it more suitable to participate in the formation of polymer electrolytes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low cost, low toxicity, stability, and ease of preparation, lithium bis(oxalato)borate (LiBOB) is currently being evaluated as a suitable salt for use in lithium ion battery technology [10]. Also compared with other Li salts, LiBOB salt has low lattice energy making it more suitable to participate in the formation of polymer electrolytes [10,11]. Ionic transport in polymer electrolyte is, however, not completely understood and remains an obstacle to achieving the required ambient conductivity [12].…”
Section: Introductionmentioning
confidence: 99%